How Did Health Care Reform in Massachusetts Impact Insurance Premiums? - Graves, John A; Gruber, Jonathan (American Economic Review, 2012)
It is widely recognized that the 2006 Massachusetts health reforms served as a blueprint for national reform under the 2010 Affordable Care Act (ACA). As such, there is interest in using the Massachusetts experience to understand how insurance premiums might change under the ACA. In this paper, we analyze changes in private insurance premiums in Massachusetts between 2002 and 2010. In contrast to earlier estimates from Massachusetts (Cogan, Hubbard and Kessler 2010), we find no statistical evidence of changes in group premiums. By contrast, we find large reductions in non-group premiums in Massachusetts relative to the rest of the U.S.